2013
DOI: 10.1016/j.jcmg.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

CV Imaging: What Was New in 2012?

Abstract: Echocardiography, single-photon emission computed tomography (SPECT), positron emission tomography (PET), cardiac magnetic resonance, and cardiac computed tomography can be used for anatomic and functional imaging of the heart. All 4 methods are subject to continuous improvement. Echocardiography benefits from the more widespread availability of 3-dimensional imaging, strain and strain rate analysis, and contrast applications. SPECT imaging continues to provide very valuable prognostic data, and PET imaging, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Of these, the absence of an assessment with cardiac magnetic resonance imaging (MRI) deserves further comment. Without doubt MRI is the gold standard for noninvasive assessment of LV morphology/function, and tissue characterization [47]. This must be taken into account in the planning of new trials.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Of these, the absence of an assessment with cardiac magnetic resonance imaging (MRI) deserves further comment. Without doubt MRI is the gold standard for noninvasive assessment of LV morphology/function, and tissue characterization [47]. This must be taken into account in the planning of new trials.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In addition, they have a superior utility in evaluating patients with left bundle branch block, ventricular paced rhythm, and left ventricular hypertrophy. Studies have linked SPECT with higher false-positive results when used to evaluate CAD patients due to limited spatial resolution in certain cases (e.g., breast attenuation, left ventricular hypertrophy) [7][8][9]. The use of the nuclear stress test is relatively safe, most of the side effects are minimal and transient, and the majority is linked to the pharmacological stressors used.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were further subdivided into four groups based on the results of the SPECT and ICA demographics as shown in Table3. The median (IQR) of total ischemia scar was 9(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and the mean of total scar size was 0.47 ± 2.01. Other characteristics of the SPECT study are shown in Table4.…”
mentioning
confidence: 99%
“…Increased left ventricle (LV) stiffness, one of the contributing factors to abnormal systolic or diastolic function, has been found in various cardiovascular diseases such as diastolic heart failure, cardiac fibrosis, steatosis, altered sarcomere activity, and hypertension . Conventionally, the primary approaches to assessing the contractility of the LV include an invasive method of measuring the pressure–volume curves over the cardiac cycle and noninvasive approaches of assessing deformation of the LV during systole and diastole, such as tagged MRI or strain and strain rate echocardiography .…”
Section: Introductionmentioning
confidence: 99%